1998
DOI: 10.1038/sj.bjp.0701720
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 suppression of acetylcholine release from parasympathetic nerves innervating guinea‐pig trachea by interacting with prostanoid receptors of the EP3‐subtype

Abstract: 1 We have demonstrated recently that exogenous prostaglandin E 2 (PGE 2 ) inhibits electrical ®eld stimulation (EFS)-induced acetylcholine (ACh) release from parasympathetic nerve terminals innervating guinea-pig trachea. In the present study, we have attempted to characterize the pre-junctional prostanoid receptor(s) responsible for the inhibitory action of PGE 2 and to assess whether other prostanoids modulate, at a prejunctional level, cholinergic neurotransmission in guinea-pig trachea. 3 H]-ACh release wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…These results indicate that EP3R may regulate the output mediated by those autonomic preganglionic neurons from the CNS. However, most of pharmacologic studies on the functions of PGE 2 in the autonomic nervous system have focused thus far on the EP3R that is located on peripheral terminals of the autonomic postganglionic nerve fibers (Mantelli et al, 1991;Molderings et al, 1992Molderings et al, , 1994Reinheimer et al, 1998;Spicuzza et al, 1998). Therefore, the distribution of EP3R-LI in this study may help to reveal the unknown roles of PGE 2 in the central autonomic system.…”
Section: Correlations Between Ep3r Distribution and Functionsmentioning
confidence: 89%
See 2 more Smart Citations
“…These results indicate that EP3R may regulate the output mediated by those autonomic preganglionic neurons from the CNS. However, most of pharmacologic studies on the functions of PGE 2 in the autonomic nervous system have focused thus far on the EP3R that is located on peripheral terminals of the autonomic postganglionic nerve fibers (Mantelli et al, 1991;Molderings et al, 1992Molderings et al, , 1994Reinheimer et al, 1998;Spicuzza et al, 1998). Therefore, the distribution of EP3R-LI in this study may help to reveal the unknown roles of PGE 2 in the central autonomic system.…”
Section: Correlations Between Ep3r Distribution and Functionsmentioning
confidence: 89%
“…Many pharmacologic studies have indicated that EP3R functions as a presynaptic receptor (Mantelli et al, 1991;Molderings et al, 1992Molderings et al, , 1994Exner and Schlicker, 1995;Reinheimer et al, 1998;Spicuzza et al, 1998). From the above-mentioned results of the dorsal rhizotomy experiments, it is inferred that the EP3R protein in the spinal dorsal horn is supplied through axons from dorsal root ganglion cells and is located on the presynaptic membrane.…”
Section: Synaptic Localization Of Ep3rmentioning
confidence: 93%
See 1 more Smart Citation
“…Inflammatory cytokines may also activate sphingomyelinase in the cell membrane to generate ceramide, which may also upregulate COX-2 independently of NF-B (Newton et al, 2000). PGE 2 is a bronchodilator of human airways and inhibits the release of proinflammatory cytokines from monocytes (Meja et al, 1997) and acetylcholine release from airway cholinergic nerves (via prostaglandin E 3 receptors) (Spicuzza et al, 1998), suggesting that it may have beneficial effects in COPD airways. Furthermore, PGE 2 markedly enhances the anti-inflammatory actions of phosphodiesterase-4 inhibitors, which are in clinical development as anti-inflammatory therapy for COPD (Au et al, 1998).…”
Section: Prostaglandin Ementioning
confidence: 99%
“…Activation of these receptors leads to protein kinase A-mediated phosphorylation of myosin light-chain kinase, which inhibits actinemyosin interactions and decreases muscle tone. PGE 2 also acts via EP 3 receptors to reduce the release of contractile neurotransmitters from parasympathetic neurons in the lung in animal models (Spicuzza et al, 1998). Similarly, prostacyclin relaxes airway smooth muscle.…”
Section: Prostanoidsmentioning
confidence: 98%